AALIANCE Ambient Assisted Living Roadmap - Broek, Ger van den (IOS Press, 2013)
In this publication a roadmap on Ambient Assisted Living (AAL) is presented. It is produced by the European Ambient Assisted Living Innovation Alliance, or AALIANCE project, funded under the 7th European Framework Programme. In the first chapter new developing trends in AAL are looked at from different perspectives and barriers to their implementation are discussed. This is followed by a detailed discussion of the application domains; AAL4persons (Chapter 2), AAL@community (Chapter 3), AAL@work (Chapter 4) and a detailed presentation of the enabling technologies - sensing, reasoning, acting, interaction and communication - (Chapter 5). The final chapter presents a way to set up an AAL system (Chapter 6). This resulted in a document that can be considered as the technology roadmap for AAL.